Perancangan Sistem Informasi E-Library pada SMK Negeri 9 Berbasis Web - Mangunsong, Patrecia; Simamora, Roni J.; Nainggolan, Rena (Universitas Methodist Indonesia, 2024)
The rapid development of information technology encourages various sectors, including education, to adopt more efficient information systems. This study aims to design and implement a web-based e-library information system at SMK Negeri 9. This system is designed to facilitate the management and access of library collections, both for students and school staff. The methodology used includes needs analysis, system design, implementation, and testing. The results of this study indicate that a web-based e-library can improve the efficiency of library management and facilitate access to information for users. This system is also equipped with book search, borrowing, returning, and member management features. It is hoped that with this e-library, it can support the teaching and learning process at SMK Negeri 9 to be more effective and efficient.